Role of Phospholipase A(2) in Retrograde Transport of Ricin - Klokk, Tove Irene (MDPI, 2011)

(untitled)
Ricin is a protein toxin classified as a bioterror agent, for which there are no known treatment options available after intoxication. It is composed of an enzymatically active A-chain connected by a disulfide bond to a cell binding B-chain. After internalization by endocytosis, ricin is transported retrogradely to the Golgi and ER, from where the ricin A-chain is translocated to the cytosol where it inhibits protein synthesis and thus induces cell death. We have identified cytoplasmic phospholipase A(2) (PLA(2)) as an important factor in ricin retrograde transport. Inhibition of PLA(2) protects against ricin challenge, however the toxin can still be endocytosed and transported to the Golgi. Interestingly, ricin transport from the Golgi to the ER is strongly impaired in response to PLA(2) inhibition. Confocal microscopy analysis shows that ricin is still colocalized with the trans-Golgi marker TGN46 in the presence of PLA(2) inhibitor, but less is colocalized with the cis-Golgi marker GM130. We propose that PLA(2) inhibition results in impaired ricin transport through the Golgi stack, thus preventing it from reaching the ER. Consequently, ricin cannot be translocated to the cytosol to exert its toxic action.